Improving Teacher Performance By Worship Motivation and Work Discipline Case Study at Bakong Pittaya School, Thailand - Rahma Izzati Fitri; Eni Candra Nurhayati; Bahtiar Effendi (Publikasi Indonesia, 2024)
This study aims to determine how work discipline and motivation affect teachers' performance. This study used total sampling for data collection, which involved distributing questionnaires and measuring the results with a Likert scale. Work discipline and motivation are the study's independent variables, and Teacher Performance is the study's dependent variable. The outcomes of this study demonstrate that work discipline and motivation both positively and significantly affect teachers' performance. Conclusion Teacher performance is significantly impacted by work discipline. This demonstrates that teachers' performance at Bakong Pittaya School in Thailand will improve the more work discipline they possess. With the T-statistic value of 6.947, the influence of work discipline is more significant than motivation.